Morphological variation, genetic diversity and phylogenetic relationships of Hypericum triquetrifolium Turra populations from Tunisia - Houda Jenfaoui (Taylor & Francis Group, 2021)
Hypericum triquetrifolium Turra is an ecologically, medicinally and economically important species in Tunisia. Thirty-six Hypericum individuals sampled from 6 northern Tunisian locations were investigated for their diversity and relationships using 10 inter-simple sequence repeats (ISSR) markers and 10 morphological features at vegetative stage. The phylogenetic analysis, using 308 bp of sequenced ITS1 region, identified the Hypericum individuals as H. triquetrifolium that clustered with members of genus Hypericum section 9, 9a, 9b and 27, in agreement with the previous molecular classification of the genus. Among the 10 ISSR markers tested, 7 were scorable and yielded 91 loci with 94.5% of polymorphism. UBC848 and UBC836 were the most polymorphic ISSR markers. The level of genetic diversity (HT = 0.247) and gene flow between the six populations (Nm = 1.169) were moderate. The structure analysis revealed three genetic subpopulations: individuals of Le Krib location formed a subpopulation divergent from two other subpopulations, probably due to its northwestern and high-altitude geographic barriers, and its sub-humid microclimate. Zaghouan, northeastern location in the lower semi-arid, with the highest genetic (I = 0.370) and morphological (I = 0.631) Shannon’s information indices and, regrouping two out of the three genetic subpopulations, is the most probable zone of origin for H. triquetrifolium. In addition, morphological data showed higher diversity than ISSR data; however, no evidence of correlation between genetic and morphologic traits could be suggested in this study. These results on the genetic diversity and phylogenetic analysis will contribute to the conservation of the gene pool of H. triquetrifolium in Tunisia.